2001
DOI: 10.1016/s0269-7491(00)00097-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient losses by surface run-off following the application of organic manures to arable land. 1. Nitrogen

Abstract: Research was conducted on nitrogen (N) surface run-off losses following organic manure applications to land, utilising a purpose-built facility on a sloping site in Herefordshire under arable tillage. Different rates and timing of cattle slurry, farmyard manure and inorganic N and phosphorus (P) fertiliser were compared, over a 4-year period (1993-97). P losses from the same studies are reported in a separate paper. The application of cattle slurries to the silty clay loam soil increased the loss of solids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 9 publications
2
47
0
3
Order By: Relevance
“…This was confirmed by Aita et al (2006) under conditions similar to the ones in this study. In addition, transfer by runoff occurred as well as reported by Ceretta et al (2010) and Smith et al (2001a). Furthermore, mineral N may be involved in transfer by ammonia volatilization, mainly from soils under no-tillage, once manure is applied onto crop residues without soil incorporation and the transferred quantities may reach 32 % of the total N applied via manure (Mkhabela et al, 2008).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…This was confirmed by Aita et al (2006) under conditions similar to the ones in this study. In addition, transfer by runoff occurred as well as reported by Ceretta et al (2010) and Smith et al (2001a). Furthermore, mineral N may be involved in transfer by ammonia volatilization, mainly from soils under no-tillage, once manure is applied onto crop residues without soil incorporation and the transferred quantities may reach 32 % of the total N applied via manure (Mkhabela et al, 2008).…”
Section: Resultssupporting
confidence: 56%
“…This rapid transformation of ammoniacal N to N-NO 3 -significantly increases the concentration of N-NO 3 -in soil (Loria & Sawyer, 2005). However, accumulation of N-NO 3 -in soil occurs in the first days after pig slurry application (Chantigny et al, 2004;Assmann et al, 2007;Adeli et al, 2008) and decreases over time due to its transfer by runoff (Smith et al, 2001a;Ceretta et al, 2010) and, mainly, percolation (Daudén et al, 2004;Basso et al, 2005;Bergström & Kirchmann, 2006), as it forms an outer-sphere complex with low binding energy with surface functional groups of reactive soil particles.…”
Section: Introductionmentioning
confidence: 99%
“…Deve-se destacar que, no presente trabalho, decorridas 4 horas da aplicação dos dejetos ao solo, ocorreu uma chuva de 40 mm (Figura 1), o que indica que parte do N aplicado com os dejetos pode ter sido perdida via escoamento superfi cial. Smith et al (2001) destacaram que o potencial de perdas de N por escoamento superfi cial, após a aplicação dos dejetos, foi maximizado quando ocorreram eventos pluviais logo após sua aplicação.…”
Section: Resultsunclassified
“…These findings suggest that the contribution of these mechanisms can be higher than expected, particularly for chemicals with a high binding potential (McLachlan et al, 2002 andPolyakov andLal, 2004). Smith et al (2001) observed relevant contributions of surface run-off including particles losses for manure applications over 2.5-3.0 t ha −1 slurry solids in UK arable lands. But due to the higher run-off/erosion risk of the Mediterranean region a lower threshold should be considered for this area (Arhonditsis et al, 2002).…”
Section: Discussionmentioning
confidence: 74%